A case report of a self-reproduced case of Paederus dermatitis - Panta, YR; Poudyal, Y (Journal of Universal College of Medical Sciences, 2014)
Many cases of irritant contact dermatitis are noted every year in the students residing at the Universal College of Medical Science (UCMS) Hostel, Bhairahawa. The exact etiology of the disease was not confirmed but the suspect was an insect Paederus', commonly referred to as 'acid fly' in UCMS. However, none of the patients ever gives the clear cut history about the time of contact with the insect after noticing the lesion. So, an experiment was performed by crushing the suspected insect on the skin of the flexor aspect of the forearm and the reactions produced on the skin and the symptoms were noted every 12 hourly till the primary lesion was formed. Erythematous papules were formed initially that passed through different stages to form an erythematous plaque with many vesicles that suppurated to form sterile pustules. This resembled the common lesions observed in the students. It was confirmed that the irritant contact dermatitis observed in the students residing at the UCMS hostel is Paederus dermatitis. The clinical course of this dermatitis was also revealed experimentally. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9575 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 48-52